Effect of aqueous extract of horse purslane (Trianthema portulacastrum L.) on germination and seedling growth of selected field crops - Rathika, S; Ramesh , Thanakkan; Kavitha , M P; Vanitha, K; Natarajan, S K; Rajakumar, D; Bhuvaneswari, J; Satheeshkumar, N; Jagadeesan, R; Dhanushkodi, V; Dinesh, G K; Vinoth, R (Plant Science Today, 2025)
An experiment was conducted during 2021 and 2022 in Anbil Dharmalingam Agricultural College and Research Institute, TNAU, Tiruchirappalli, to know the overall allelopathic impact of horse purslane on the germination and seedling growth of rice, ragi, maize, green gram and sunflower. A Completely Randomised Design (CRD) was used to test 6 treatments, including a control and 1%, 2%, 3%, 4% and 5% concentrations of horse purslane whole-plant extract, with 4 replications. Seed germination and subsequent growth and development of selected crops were negatively affected by the extract of horse purslane. The minimum germination was recorded in 5% horse purslane extract, while maximum germination was recorded in control. A consistent decline in germination percentage was observed with increasing extract concentrations. The extract of horse purslane significantly reduced the root length, shoot length, seedling length and seedling vigour index (SVI) of the tested crops. The highest seedling mortality rates were observed at the 5% extract concentration, with values of 83.8%, 78.9%, 47.3%, 51.6% and 81.3% for rice, ragi, maize, sunflower and green gram respectively. The study indicates that horse purslane needs to be controlled effectively in the cropped fields, otherwise, it could reduce the growth and development of field crops. The allelochemicals in horse purslane present significant opportunities for further research on their impact on other weed species, which could contribute to the development of effective weed management strategies in field crops.